Crimean-Congo hemorrhagic fever: a growing threat to Europe - Freitas, Natalia; Legros, Vincent; Cosset, François-Loïc (Comptes Rendus Biologies, 2022)
Tick-borne infectious diseases are increasing, driven by geographic expansion of ticks. Crimean-Congo hemorrhagic fever virus (CCHFV) is a tick-borne virus of the family Nairoviridae that poses serious threat to public health. CCHFV can cause severe forms of hemorrhagic fever with high case fatality rates (CFR) (10–40%) and can be transmitted from human to human. Until a few years ago, no cases of CCHF had been reported in western Europe. However, high seropositivity rates in wildlife and detection of multiple strains of CCHFV in ticks in Spain suggest that CCHFV enzootic cycle has been established in some areas of southwestern Europe. As far as CCHFV-associated morbidity and mortality are concerned, there are no approved therapeutic options or US/EU licensed vaccines for treatment. Here we discuss some eco-epidemiological aspects as well as public health and socio-economic impacts associated with CCHFV circulation and outbreaks. We also emphasize that it has become essential to identify key inter-species transmission processes of this group of pathogens, to understand basic molecular mechanisms of their replication, and to define their pathogenic potentials.